2020
DOI: 10.1177/0032258x20926939
|View full text |Cite
|
Sign up to set email alerts
|

Community police academies: Assessing the effect of education on public perceptions of police

Abstract: Citizens often have misconceptions about law enforcement. This misinformation may contribute to distrust and heightened concerns about force and misconduct. Agencies attempt to address this by promoting procedural justice and providing community education on police practices. Thus far, past research has not been clear on the actual utility of community education on changing public perceptions. Recent funding has allowed one department to host 14 one-day community police academies (CPAs) to educate residents ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 27 publications
(41 reference statements)
3
12
0
Order By: Relevance
“…Some anecdotal evidence suggests that exposing people to use of force training can improve knowledge about the use of force (e.g., Nicholson, 2018), but it is unclear if such an intervention can be scaled up. Citizen academies are also used in some jurisdictions to educate the public about policing issues, including the use of force, but to date there have been few evaluations of their impact (however, see Perez, Nguyen, & Vogel, 2020). Our own work in this area has shown lengthy interventions (e.g., lectures on the use of force) can enhance knowledge and change attitudes about police use of force in a student sample, but questions remain about whether these results generalize to the wider public, remain stable over time, can be found for shorter interventions, or predict other outcomes, such as increased trust in the police.…”
Section: Commentary #9 By Chief Adam Palmer: Using Use Of Force Data and Research To Further Public Confidence In The Policementioning
confidence: 99%
“…Some anecdotal evidence suggests that exposing people to use of force training can improve knowledge about the use of force (e.g., Nicholson, 2018), but it is unclear if such an intervention can be scaled up. Citizen academies are also used in some jurisdictions to educate the public about policing issues, including the use of force, but to date there have been few evaluations of their impact (however, see Perez, Nguyen, & Vogel, 2020). Our own work in this area has shown lengthy interventions (e.g., lectures on the use of force) can enhance knowledge and change attitudes about police use of force in a student sample, but questions remain about whether these results generalize to the wider public, remain stable over time, can be found for shorter interventions, or predict other outcomes, such as increased trust in the police.…”
Section: Commentary #9 By Chief Adam Palmer: Using Use Of Force Data and Research To Further Public Confidence In The Policementioning
confidence: 99%
“…One approach that law enforcement agencies use to educate the public are community police academies (CPAs). Past research has indicated that CPA events, which aim to improve public education on police practices and enhance police-community relationships, can be effective (Bonello and Schafer 2002; Breen and Johnson, 2007; Brewster et al ., 2005; Perez et al ., 2020a). This research, however, often takes place directly following participation in CPA events.…”
Section: Introductionmentioning
confidence: 99%
“…Police departments throughout the United States have adopted various strategies to improve the relationship between citizens and law enforcement (for a more thorough review of these initiatives, see: Perez et al ., 2020a; 2020b). These strategies involve the community policing principle that highlights the value of building partnerships with the community as a method to combat crime and other social problems (Cohn, 1996; McCandless, 2018, Trojanowicz and Bucqueroux, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations